2009
DOI: 10.1111/j.1439-0531.2009.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Postpartum Ovulation on Fertility in Dairy Cows

Abstract: Our objectives were to determine the effects of early ovulation on fertility and uterine health of dairy cows. Four hundred and forty-five Holstein cows (185 primiparous and 260 multiparous) from five herds were used. Blood samples were collected at 21, 35 and 49 days in milk (DIM) and cows were considered to be cyclic at 21 DIM (Cyc21) if serum progesterone (P4) concentration was above 1 ng/ml, cyclic by 49 DIM (Cyc49) if P4 concentration was above 1 ng/ml at 35 or 49 DIM, or not cyclic (NotCyc) if P4 concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
91
9
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 29 publications
16
91
9
2
Order By: Relevance
“…(Table 2). Galvao et al (2010) published a study on the positive role of the earlier 1 st ovulation on subsequent fertility, which was also found in our experiment. Animals ovulating follicles from the 1 st follicular wave (G1 group) got pregnant earlier (mean DO for G1, G2, and G3 were 84, 113, and 164 days, respectively; P = 0.07) and after a voluntary waiting period they were not hormonally treated as often as cows ovulating later pp (frequency of hormonal treatment was 1, 8, and 5 animals for G1, G2, and G3, respectively; P = 0.008).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…(Table 2). Galvao et al (2010) published a study on the positive role of the earlier 1 st ovulation on subsequent fertility, which was also found in our experiment. Animals ovulating follicles from the 1 st follicular wave (G1 group) got pregnant earlier (mean DO for G1, G2, and G3 were 84, 113, and 164 days, respectively; P = 0.07) and after a voluntary waiting period they were not hormonally treated as often as cows ovulating later pp (frequency of hormonal treatment was 1, 8, and 5 animals for G1, G2, and G3, respectively; P = 0.008).…”
Section: Resultssupporting
confidence: 85%
“…In the context of the onset of ovarian activity pp, authors have focused mainly on indicators such as dynamics and metabolic/hormonal profiles of the first follicular wave (Kawashima et al, 2007), days of the first ovulation (Galvao et al, 2010), the first onset of luteal activity (Hayashi et al, 2008), links to uterine involution (Sheldon and Dobson, 2004) or to the first insemination term (Hommeida et al, 2005). It has been determined that the first follicular growth wave emerges soon after delivery and is independent of the EB of the animal (Butler, 2003).…”
mentioning
confidence: 99%
“…In general, fertility is greater in cows that ovulate sooner after parturition (Butler, 2003;Bossaert et al, 2008;Galvão et al, 2010b). During early postpartum NEB, the pulse frequency of LH release, the size and development rate of follicles, concentrations of estrogen and progesterone, and size of the CL all are decreased (Jorritsma et al, 2003;Garnsworthy et al, 2008).…”
Section: Neb and Impaired Fertilitymentioning
confidence: 99%
“…Although studies have demonstrated a weak and variable relationship between the degree of NEB and impaired fertility, the time to NEB nadir and the direction and/or rate of change in NEB appear to be stronger indicators (Whitaker et al, 1993;Butler, 2003;Reist et al, 2003). Possible mechanisms for detrimental effects of NEB on reproduction include (1) delayed resumption of ovarian cyclicity, through effects on hypothalamic, pituitary and ovarian function, (2) impacts on oocyte or corpus luteum (CL) 'quality', viability, or function, sometimes referred to as 'follicular memory' and (3) development of fatty liver (hepatic lipidosis).In general, fertility is greater in cows that ovulate sooner after parturition (Butler, 2003;Bossaert et al, 2008;Galvão et al, 2010b). During early postpartum NEB, the pulse frequency of LH release, the size and development rate of follicles, concentrations of estrogen and progesterone, and size of the CL all are decreased (Jorritsma et al, 2003;Garnsworthy et al, 2008).…”
mentioning
confidence: 99%
“…Cows that developed metritis had decreased (P ≤ 0.05) TNFα gene expression at 0, 7, and 14 days after calving, and decreased IL-1β and IL-6 at 7 and 14 days after calving compared to cows that had endometritis and control cows. Adapted from Galvão et al (105).…”
Section: Mechanism Of Recognition Of Pathogens By Professional Phagocmentioning
confidence: 99%